Ч. 2; Физика - Вайсбурд Д. И. Давид Израйлевич; Лельчук Л. Ю. Лариса Юрьевна; Сивов Ю. А. Юрий Александрович; Тюрин Ю. И. Юрий Иванович; Чебодаев М. И. Михаил Иванович (2009, 2009)
Заглавие с титульного экрана